Advanced Intrahepatic Cholangiocarcinoma: Post Hoc Analysis of the ABC-01, -02, and -03 Clinical Trials. (11th May 2019) - Lamarca, Angela; Ross, Paul; Wasan, Harpreet S; Hubner, Richard A; McNamara, Mairéad G; Lopes, Andre; Manoharan, Prakash; Palmer, Daniel; Bridgewater, John; Valle, Juan W
Abstract: Background: The incidence of intrahepatic cholangiocarcinoma (iCCA) is increasing. The aim of the study was to provide reference survival data for patients with advanced iCCA treated with first-line cisplatin-gemcitabine chemotherapy (current standard of care). Methods: Individual data from patients with iCCA recruited into the prospective, random assignment Advanced Biliary Tract Cancer (ABC)-01, -02, and -03 studies were retrieved. The prevalence and survival of liver-only iCCA was also assessed. Survival analysis was performed using univariate and multivariable Cox regression. All statistical tests were two-sided. Results: Of 534 patients recruited into the ABC-01, -02, and -03 studies, 109 (20.4%) had iCCA. Most patients (n = 86, 78.9%) had metastatic disease at the time of recruitment; 52 patients (47.7%) had liver-only disease. Following random assignment, 66 (60.6%) iCCA patients received cisplatin and gemcitabine. The median progression-free and overall survival (OS) were 8.4 months (95% confidence interval [CI] = 5.9 to 8.9 months) and 15.4 months (95% CI = 11.1 to 17.9 months), respectively. Of these 66 patients, 34 patients (51.5%) had liver-only disease. Following chemotherapy, 30 (45.5%) and 21 (31.8%) were progression-free at 3 and 6 months from chemotherapy commencement, respectively. The median OS for patients with liver-only iCCA at diagnosis and after 3 and 6 months of chemotherapy was 16.7 months (95% CI = 8.7 to 20.2 months), 17.9 months (95% CI = 11.7 to 20.9 months), and 18.9 months (95% CI = 16.7 to 25.9 months), respectively. Multivariable analysis confirmed that iCCA had a longer OS compared with other non-iCCA biliary tract cancers (hazard ratio = 0.58, 95% CI = 0.35 to 0.95, P value = .03); liver-only iCCA patients also showed longer OS even though findings did not reach statistical significance (hazard ratio = 0.65, 95% CI = 0.36 to 1.19, P value = .16). Conclusions: Patients diagnosed with advanced iCCA have a better OS compared with other biliary tract cancers; a similar trend was identified for patients diagnosed with liver-only iCCA. These findings are to be considered for future clinical trial design.